Labor economics in an Islamic framework : theory and practice /: theory and practice. (2021) - Azid, Toseef; Burki, Umar; Khawaja, Muhammad Junaid; Shirazi, Nasim Shah; Ṭāhir, Muḥammad
No abstract available